Utiliza????o de informa????es patent??rias na busca de solu????es inovadoras para o setor de atendimento hospitalar - Ram??o, Gleber Batista (2017)
The search for innovations and new technologies can contribute to improvements in the current conditions of the emergency and emergency sectors, which are currently very precarious in most Brazilian hospitals, both in the public health sector and in the private sector, , or even neglected. In this context, they arise as patents, which carry with them a description of various technologies, and in turn are capable of representing the status of a nation's financial and technological development. The use of patent information is still incipient in the country, and these are practically not used to solve the problems present in most organizations. The patent bases are non-referential bases, where it is necessary to use computational tools that allow the extraction and massive analysis of information present in patent documents, since the manual accomplishment of said process is impossible, especially due to the enormous amount of patents available for consultation. Thus, the central focus of the present work is to use the Patent2net computational tool, a free patent mining software, to extract from the Espacenet database patent documents that contain information relevant to the solution of some problems present in the daily routine of hospital care. After evaluating the main problems observed in these sectors of a large public hospital in the capital of S??o Paulo, five subjects were considered of major relevance: 1 - difficulties in the execution of bedridden patients; 2 - problems in the drainage of gastric contents; 3 - difficulties in locating veins for medication administration; 4 - many cases of pressure ulcers; 5 - difficulties in performing oral hygiene in intubated patients or with difficult access to the oral cavity. The use of Patent2net focused on the search for free patents for reproduction in Brazil and with potential for frugality, ie, inclusive patents and presenting low reproduction cost, it being possible to locate 4 patents with these characteristics, with the exception of device technology of vein placement. As a contribution of the present work, a tool is presented that is easy to use and accessible to all who are interested in searching for patents, on any desired subjects. In addition, through this technometric study, patents have been identified that can assist in the care of severely ill patients, in critical units in hospitals or emergency and emergency care in Brazil.